2017
DOI: 10.4314/sokjvs.v15i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Swine farm infestation with <i>Culicoides</i> species (biting midges) in Zaria, Nigeria

Abstract: Collection of biting midges within a piggery farm using black-light suction traps revealed the presence of diverse species of Culicoides. Out of a total of one thousand four hundred and five (1,405) midges caught, one thousand three hundred and sixty-six (1,366) were identified as species in the genus Culicoides while the remaining thirtynine (39) were unidentified members in the family Ceratopogonidae. The identified Culicoides were further classified into eight species based on their morphological characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Both the dorsal and ventral abdominal structures revealed evidence of functionality due to presence of functional spermathecae (three each on the dorsal and ventral abdominal segments for the Culicoides oxystoma specimen (total six) and two functional spermathecae for the C imicola sample. A comparison was made between the gynander and a typical male and female specimen of the same species reported by Oke et al (2016 and2017). It was observed that the gynander has combined characteristics typical of both male and female.…”
Section: Resultsmentioning
confidence: 88%
“…Both the dorsal and ventral abdominal structures revealed evidence of functionality due to presence of functional spermathecae (three each on the dorsal and ventral abdominal segments for the Culicoides oxystoma specimen (total six) and two functional spermathecae for the C imicola sample. A comparison was made between the gynander and a typical male and female specimen of the same species reported by Oke et al (2016 and2017). It was observed that the gynander has combined characteristics typical of both male and female.…”
Section: Resultsmentioning
confidence: 88%
“…Culicoides and Tabanidae also need to be considered. Culicoides, ranked fourth in the expert elicitation, have been shown to be able to feed on pigs (Bartsch, Bauer, Wiemann, Clausen, & Steuber, 2009) and are known to be present in pig farms (Kirkeby, Bodker, Stockmarr, Lind, & Heegaard, 2013;Oke, Oke, & Adejinmi, 2017;Zimmer et al, 2008 Perie, Chermette, Millemann, & Zientara, 2005), so that a blood meal on a host with low viremia might probably not result in the ingestion of a sufficient dose of virus to initiate replication and spread of the virus in the vector. In case of massive Culicoides infestations, they may also play a role in the mechanical transmission of ASFV.…”
Section: Discussionmentioning
confidence: 99%
“…Although having a slightly lower median score in the ranking, Culicoides and Tabanidae also need to be considered. Culicoides , ranked fourth in the expert elicitation, have been shown to be able to feed on pigs (Bartsch, Bauer, Wiemann, Clausen, & Steuber, 2009) and are known to be present in pig farms (Kirkeby, Bodker, Stockmarr, Lind, & Heegaard, 2013; Oke, Oke, & Adejinmi, 2017; Zimmer et al, 2008). Assuming that Culicoides are competent vectors for ASFV, it is mainly their high abundance that would contribute to their vectorial capacity.…”
Section: Discussionmentioning
confidence: 99%